Pengaturan Sanksi Tentang Anggaran Dasar Perseroan Yang Tidak Dikonversikan Pada Klasifikasi Baku Lapangan Usaha Indonesia 2020 - Surya Lestari, Ida Ayu Gede Sinta; Mayasari, I Dewa Ayu Dwi (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 02 (2022), 2022)
The purpose of this paper is to find out the process of classifying and setting sanctions on the articles of association of companies whose business fields are not converted to the KBLI 2020. This study uses a normative legal research method with the problem of void norms with the type of approach to legislation and legal concepts. The results show that in the process of classifying the business fields of the company's articles of association must be in accordance with Article 3 of the articles of association guided by the 2020 KBLI, then can register for legalization of establishment on the AHU system and will automatically be integrated with the OSS system. For the company still using the 2017 KBLI, the company must convert the 2020 KBLI, by changing its articles of association and registering electronically through the AHU system. And, with regard to companies that do not convert their business fields, there are no sanctions arrangements against the company and it creates legal uncertainty, so that the company cannot manage business licenses, cannot cooperate with government and private agencies, and does not have legality in Indonesia and potential for criminal activity.